Efektivitas Media Loose Parts di PAUD Kelompok A Pada Masa Belajar Dari Rumah - Siskawati, Siskawati; Herawati, Herawati (Jurnal Pendidikan Luar Sekolah, 2021)
Loose parts media are removable objects that can be used as a media for constructive play by combining, making arrangements, assembling, and so on according to children's wishes to optimize development, one of which is creativity. This study aims to determine the effectiveness of the use of loose parts media during the Learning from Home (BDR) period for group A children at PAUD Tahfidz Al-Hasan Ciampea. The research data were collected using interview and observation instruments. The results showed that the use of loose parts media during the Learning from Home (BDR) period was quite effective in increasing the creativity of early childhood. The use of loose parts media during the Learning from Home (BDR) period can improve children's creativity, cooperative attitude, socialization and communication skills and can also develop optimally. In addition, loose parts media is quite effective in assisting teachers in providing material to children and can make it easier for parents to accompany children during the Learning from Home (BDR) period. Besides being able to improve student learning outcomes, loose parts media are also easy to find in the environment around the child's residence without spending money. AbstrakMedia loose parts merupakan benda-benda lepasan yang dapat digunakan sebagai media permainan konstruktif dengan mengombinasi, membuat susunan, merakit, dan lain sebagainya sesuai dengan keinginan anak untuk mengoptimalkan perkembangan salah satunya kreativitas. Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan media loose parts selama masa Belajar Dari Rumah (BDR) pada anak kelompok A di PAUD Tahfidz Al-Hasan Ciampea. Data penelitian dikumpulkan dengan menggunakan instrumen wawancara dan observasi. Hasil penelitian menunjukkan bahwa, penggunaan media loose parts selama masa Belajar Dari Rumah (BDR) cukup efektif untuk meningkatkan kreativitas anak usia dini. Penggunaan media loose parts pada masa Belajar Dari Rumah (BDR) dapat meningkatkan kreativitas, sikap kooperatif, sosialisasi dan keterampilan komunikasi anak secara optimal. Selain itu, media loose parts cukup efektif membantu guru dalam memberikan materi kepada anak dan dapat mempermudah orang tua dalam mendampingi anak-anak selama masa Belajar Dari Rumah (BDR). Selain dapat meningkatkan capaian hasil pembelajaran siswa, media loose parts juga mudah ditemukan dilingkungan sekitar tempat tinggal anak tanpa mengeluarkan biaya.